Defining, Understanding, and Supporting Open Collaboration: Lessons From the Literature. (May 2013) - Forte, Andrea; Lampe, Cliff
In this short introductory piece, we define open collaboration and contextualize the diverse articles in this special issue in a common vocabulary and history. We provide a definition of open collaboration and situate the phenomenon within an interrelated set of scholarly and ideological movements. We then examine the properties of open collaboration systems that have given rise to research and review major areas of scholarship. We close with a summary of consistent findings in open collaboration research to date.